Case Report: Use of extracorporeal support to treat a fulminant Mycobacterium bovis infection and complex broncho-oesophageal fistula in a child - Hussein, Hussein; Paget, Richard; Grandjean, Louis; Bamford, Alasdair; Pandey, Ashwin; Fidler, Katy; Snowden, Claire; Beeman, Arun; Shetty, Pooja; Muthialu, Nagarajan (Frontiers in Pediatrics, 2025)
Tuberculosis (TB), caused by Mycobacterium tuberculosis remains a significant public health issue. Human TB caused by Mycobacterium bovis (M. bovis) is rare accounting for less than 1% of TB cases in UK annually. Tuberculosis secondary to immunomodulating agents is well described. We present a case of airway and pulmonary TB caused by M. bovis, likely due to zoonotic transmission, in an immunocompromised child due to medical management of Crohn's disease. Management required extracorporeal membrane oxygenation for complex surgical interventions on airway and oesophagus.